Preparation and in vivo evaluation of multifunctional 90Y‐labeled magnetic nanoparticles designed for cancer therapy. Issue 1 (20th March 2014) - Radović, Magdalena; Calatayud, María Pilar; Goya, Gerardo Fabián; Ibarra, Manuel Ricardo; Antić, Bratislav; Spasojević, Vojislav; Nikolić, Nadežda; Janković, Drina; Mirković, Marija; Vranješ‐Đurić, Sanja
Abstract Two different types of magnetic nanoparticles (MNPs) were synthesized in order to compare their efficiency as radioactive vectors, Fe3O4‐Naked (80 ± 5 nm) and polyethylene glycol 600 diacid functionalized Fe3O4 (Fe3O4‐PEG600) MNPs (46 ± 0.6 nm). They were characterized based on the external morphology, size distribution, and colloidal and magnetic properties. The obtained specific power absorption value for Fe3O4‐PEG600 MNPs was 200 W/g, indicated their potential in hyperthermia based cancer treatments. The labeling yield, in vitro stability and in vivo biodistribution profile of 90Y‐MNPs were compared. Both types of MNPs were 90Y‐labeled in reproducible high yield (>97%). The stability of the obtained radioactive nanoparticles was evaluated in saline and human serum media in order to optimize the formulations for in vivo use. The biodistribution in Wistar rats showed different pharmacokinetic behaviors of nanoparticles: a large fraction of both injected MNPs ended in the liver (14.58%ID/g for 90Y‐Fe3O4‐Naked MNPs and 19.61%ID/g for 90Y‐Fe3O4‐PEG600 MNPs) whereas minor fractions attained in other organs. The main difference between the two types of MNPs was the higher accumulation of 90Y‐Fe3O4‐Naked MNPs in the lungs (12.14%ID/g vs. 2.00%ID/g for 90Y‐Fe3O4‐PEG600 MNPs) due to their in vivo agglomeration. The studied radiolabeled magnetic complexes such as 90Y‐Fe3O4‐PEG600 MNPs constitute a great promise for multiple diagnostic‐therapeutic uses combining, for example, MRI‐magnetic hyperthermia and regional radiotherapy. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 126–134, 2015.